Phylogeography and thermal physiology of Meroles knoxii (Family: Lacertidae) : relevance for species responses to climate change - Strauss, Paula (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.